Why do some perfectionists procrastinate? The role of using effective time management strategies and perceived busyness in perfectionism outcomes - YU, Xinyao (Institutional Knowledge at Singapore Management University, 2022)
In many achievement-driven societies, maintaining productivity amidst an increasingly busy and stressful schedule has become a challenge for many people, particularly those with perfectionistic tendencies. Across two studies, the present research examined why some perfectionists are more prone to procrastination and tested the effectiveness of time management intervention in reducing their procrastination tendencies. Specifically, the current studies adopted a multidimensional approach to measure perfectionism as manifested in perfectionistic strivings and perfectionistic concerns. Study 1 showed that perfectionistic strivings negatively predicted procrastination, while perfectionistic concerns positively predicted procrastination, through the mediating effects of using effective time management strategies. Study 2 further found that time management intervention was effective in reducing procrastination regardless of people’s perfectionism tendencies. More importantly, time management intervention was deemed more beneficial when individuals with high perfectionistic concerns experienced high levels of busyness. The findings show the promise of using effective time management strategies in helping individuals with perfectionistic concerns alleviate procrastination and promote productivity.